2023
DOI: 10.1002/aelm.202201227
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Spectroscopy on Hafnium Oxide‐Based Memristive Devices

Abstract: Memristive devices for neuromorphic computing have been attracting ever growing attention over the last couple of years. In neuromorphic electronics, memristive devices with multi‐level resistance states are required to accurately reproduce synaptic weights. Here, a memristive device based on a multilayer oxide system (Nb/NbOx/Al2O3/HfO2/Au), which features a filamentary‐free, homogenous interfacial resistive switching mechanism, is investigated. To gain a deeper insight into the switching mechanism, impedance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The worked-out model is in agreement with the companion paper Marquardt et al that exploits ImpSpec to probe the current transport and switching kinetics of the same devices. [74] Based on two different experimental approaches (XPS/HAXPES and ImpSpec), our findings strongly indicate an electronic charging and discharging of traps as the fundamental origin of resistive switching in our devices, instead of ionic drift.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The worked-out model is in agreement with the companion paper Marquardt et al that exploits ImpSpec to probe the current transport and switching kinetics of the same devices. [74] Based on two different experimental approaches (XPS/HAXPES and ImpSpec), our findings strongly indicate an electronic charging and discharging of traps as the fundamental origin of resistive switching in our devices, instead of ionic drift.…”
Section: Discussionmentioning
confidence: 52%
“…This is consistent with the results of ImpSpec conducted on the reference devices, performed by Marquardt et al and reported in the companion paper. [74] Here, the kinetics of the set process and of the retention imply charging of traps rather than ion movement. Furthermore, quantitative model parameters describing current transport in HRS and LRS and switching dynamics are given.…”
Section: Device Modelmentioning
confidence: 99%
See 1 more Smart Citation